2009
DOI: 10.2337/dc09-1881
|View full text |Cite
|
Sign up to set email alerts
|

An Internet-Based Program to Improve Self-Management in Adolescents With Type 1 Diabetes

Abstract: OBJECTIVETo report results from YourWay, an Internet-based self-management intervention for adolescents with type 1 diabetes.RESEARCH DESIGN AND METHODSA total of 72 adolescents with type 1 diabetes, ages 13–17 years, were randomized to a usual-care-plus-Internet support or a usual-care group. The intervention was designed to enhance problem-solving barriers to self-management. A1C was obtained from medical records, and problem-solving and self-management were obtained via adolescent report.RESULTSGroup differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
182
0
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(200 citation statements)
references
References 15 publications
(15 reference statements)
1
182
0
3
Order By: Relevance
“…The use of personal narratives and peer-based learning has been employed successfully in behavioral interventions for other health related challenges, such as substance abuse and self-management of diabetes. [71][72][73] Cultural tailoring and message framing of interventions have also been used successfully in conjunction with educational material for VHPs. Additionally, most behavioral researchers would encourage researchers interested in implementing interventions for behavioral change to utilize a theoretical model to provide a framework for development; however, few of the studies identified in this review discussed the use of a theoretical model.…”
Section: Discussionmentioning
confidence: 99%
“…The use of personal narratives and peer-based learning has been employed successfully in behavioral interventions for other health related challenges, such as substance abuse and self-management of diabetes. [71][72][73] Cultural tailoring and message framing of interventions have also been used successfully in conjunction with educational material for VHPs. Additionally, most behavioral researchers would encourage researchers interested in implementing interventions for behavioral change to utilize a theoretical model to provide a framework for development; however, few of the studies identified in this review discussed the use of a theoretical model.…”
Section: Discussionmentioning
confidence: 99%
“…management [4][5][6]. Several studies, including our own, have shown that adopting a u-healthcare system in diabetes management helps patients improve their glucose control and reduce side effects such as hypoglycemia or weight gain [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…represented 2848 children and young people ranging from 18 to 433 per study; an inclusion of 25 to 99% of those eligible to participate (eligibility to participate was not reported in eight studies Horan et al, 1990;Joshi et al, 2009;Mosnaim et al, 2008;Mulvaney et al, 2010;Shegog et al, 2001;Yoon & Godwin, 2007). A sample size calculation was only made in 12 (44%) studies Franklin et al, 2006;Guendelman et al, 2002;Iafusco et al, 2011;Jan et al, 2007;Jones et al, 2010;Krishna et al, 2003;McPherson et al, 2006;Mosnaim et al, 2008;Palermo et al, 2009;Shegog et al, 2001;Zorc et al, 2009).…”
Section: Identified Studiesmentioning
confidence: 98%